Evaluation of Teaching Mobilities in the Context of Intercultural Education - Aikaterini Tsekou; Foulidi Xanthippi; Αnastasia Papadopoulou (Journal of General Education and Humanities, 2023)
This specific intervention aims to limit the rates of school dropout. In order to limit the rates of school dropout and to increase the school performance of students with different cultural characteristics, who attend the schools of the Directorate of Secondary Education of West Attica in the school years 2021- 2022, mobilities were implemented in the context of the Erasmus program following intercultural education. Implementing the mobilities was deemed necessary because in the cities of West Attica, during the same period, incidents of delinquency, violence, and battles took place daily between different foreigners or between foreigners and Greeks or Roma. The implementing method of the intervention is an observation with a structured observation sheet with open-ended questions. Positive results, coming out of the mobilities, were that the teachers who served in those schools, who did not always have the required knowledge in intercultural education, were made aware and trained in the effective management of heterogeneity both in students and in their parents for the benefit not only of the school community but more broadly of society—the consequences of this action concern the parents of the children and the society in general.